Comparision of Mechanical Thrombectomy With Contact Aspiration or Stent Retriever in Patients With Large-vessel Occlusion in Acute Ischemic Stroke. Issue 4 (June 2021) - Xia, Lei; Zhao, Piao-Ping; Sun, He-Xiang; Jing, Chao-Hui; Zhong, Jun; Hua, Xu-Ming; Wan, Liang
Abstract : Objectives: Whether the direct aspiration approach of thrombectomy for recanalization in patients with acute ischemic stroke has a similar efficacy and safety compared to the stent-retriever still remains uncertain. Methods: A retrospective data analysis was performed to identify patients with large cerebral artery acute ischemic stroke treated with endovascular thrombectomy. The study was conducted between January 2018 and December 2019 in a single stroke center. Results: Twenty patients met inclusion criteria for this study with a mean age 66.64 ± 17.92 years' old. The symptom occurred on the left side were in 13, and the right side in 7. The location of occlusion was 8 in M1 of the middle cerebral artery of M2, and 6 in internal carotid artery. Nine patients were randomized to first-line treatment with contact aspiration and eleven to first-line treatment with a stent retriever. The mean time from admission time to groin puncture was 55.51 ± 31.03 minutes. The average time from groin puncture to maximal revascularizion after mechanical thrombectomy was 50.9 ± 22.5 minutes in contact aspiration group, but this time was 71.37 ± 25.45 minutes in the group of stent retriever. The overall successful revascularization rate (TICI 2b-3) was 88.9% in contact aspiration (TICI2a = 1, TICI 2b = 4 patients, TICI 3 = 4 patients), and 90.1% in stent retriever (TICI2a = 1, TICI 2b = 6 patients, TICI 3 = 4 patients). Discussion: First-line thrombectomy with contact aspiration did not result in a higher successful revascularization rate at the end of the procedure but had a short time from groin puncture to maximal revascularizion. Abstract : Supplemental Digital Content is available in the text